The Hegemonic Competition in the Indo Pacific Region: Backdrop of U.S-China - Mizan, Md.Mizanur Rahman (International Journal of Sustainable Applied Sciences, 2023)
In recent years,world scholars and policy elites have emphasize the powerful systematic struggle between the united states and china on the indo Pacific region. Both china and united states implication to the own views foreign policy. Many of the possibility creation under the competitive situation through the maintain of both states on south-east and south-asia.This article visions to offer describing of the Chinese views and the hegemonic competition on the indo Pacific region. In the perspectives of most scholars and observers the systematic reach out the U.S-China is inevitable on the indo Pacific regional activities into the both powerful states. The U.S China has existing situation views into much of the factors such as the ideological disagreement,power struggle disagreements on indo-pacific region.Chinese observers intent that economic and technological system between the united states and china has the most privacy and the focus point of indo-pacific region. Meanwhile definite U.S scholars join the greater importance of U.S-China struggle over international leadership and prestige. However U.S analysts can not fully pessimistic about the aspiration for china U.S relations and have the policy recommendations maintaining the systematic zone under the U.S-China on indo Pacific region.